THERAPY OPTIMIZATION OF INFLUENZA AND OTHER ACUTE RESPIRATORY VIRAL INFECTIONS IN PEDIATRIC PRACTICE - G. P. Martynova; Ya. A. Bogvilene; I. A. Soloveva; I. A. Kutischeva; T. A. Kartel; I. Yu. Hohlova (Union of pediatricians of Russia, 2012)
The results of studies of the safety and clinical efficacy of interferon inducer in influenza and other acute respiratory viral infections in children aged 7-14 years are presented. It is shown that the antiviral immunostimulating agent reduces main symptoms of the disease, prevents the development of complications and can be recommended for use in pediatric patients for the treatment of influenza and other acute respiratory viral infections.